Feasibility Study of Vacuum Pressure Swing Adsorption for CO2 Capture From an SMR Hydrogen Plant: Comparison Between Synthesis Gas Capture and Tail Gas Capture - Chen, Yan; Ahn, Hyungwoong (Frontiers in Chemical Engineering, 2021)
In this paper, a feasibility study was carried out to evaluate cyclic adsorption processes for capturing CO2 from either shifted synthesis gas or H2 PSA tail gas of an industrial-scale SMR-based hydrogen plant. It is expected that hydrogen is to be widely used in place of natural gas in various industrial sectors where electrification would be rather challenging. A SMR-based hydrogen plant is currently dominant in the market, as it can produce hydrogen at scale in the most economical way. Its CO2 emission must be reduced significantly by its integration with CCUS. Two Vacuum Pressure Swing Adsorption (VPSA) systems including a rinse step were designed to capture CO2 from an industrial-scale SMR-based hydrogen plant: one for the shifted synthesis gas and the other for the H2 PSA tail gas. Given the shapes of adsorption isotherms, zeolite 13X and activated carbon were selected for tail gas and syngas capture options, respectively. A simple Equilibrium Theory model developed for the limiting case of complete regeneration was taken to analyse the VPSA systems in this feasibility study. The process performances were compared to each other with respect to product recovery, bed productivity and power consumption. It was found that CO2 could be captured more cost-effectively from the syngas than the tail gas, unless the desorption pressure was too low. The energy consumption of the VPSA was comparable to those of the conventional MDEA processes.